OC-064 Risk Factors for Colorectal Neoplasia in Ulcerative Colitis: Results from the Largest and Longest-Running Colonoscopic Surveillance Program. (17th August 2016) - Choi, CHR; Al Bakir, I; Ding, NSJ; Moorghen, M; Warusavitarne, J; Thomas-Gibson, S; Saunders, B; Rutter, M; Graham, T; Hart, A
Abstract : Introduction: Whilst patients with ulcerative colitis (UC) have an increased risk of developing colorectal cancer (CRC), its absolute risk remains very low. As most CRCs develop from pre-existing dysplasia, identifying those patients at high risk of developing dysplasia is important. The aim of this study was to identify risk factors associated with development of colorectal neoplasia (CRN) in patients with UC. Methods: Patients with extensive UC who were under surveillance from 2003 to 2012 were identified and followed up to July 2013. Each surveillance episode was scored for endoscopic and histological severity of inflammation based on the segment worst affected by colitis: (0, normal/quiescent; 1, mild; 2, moderate; 3, severe active). Potential predictors (n = 18) were correlated against colorectal neoplasia (CRN) outcome, which was defined as non-polypoid low-grade dysplasia, high-grade dysplasia or CRC. To take into account the variables that may change over time, we employed Cox-regression analysis with time-dependent covariates. Results: A total of 987 UC patients underwent 6, 985 colonoscopies (median, 6; interquartile range (IQR), 4–9 per patient) over 12, 305 patient-years (median follow-up, 11; IQR, 7–17) since starting their surveillance. Of these, 97 (9.8%) developed CRN (41 cancers). After multivariate analysis, following variables remained as significant contributory factor for the CRN outcome: increased average histological inflammation score (average- HIS ; average score of all surveillance colonoscopies for each patient ), endoscopic signs of disease chronicity (i.e. tubular, featureless or shortened colon), colonic stricture and primary sclerosing cholangitis (Table 1 ). Furthermore, while average-HIS was the most influential predictor, HIS of the immediately preceding colonoscopy showed comparable predictive value (Table 1 ). Post-inflammatory polyps and scarring were not significant at multivariate level. Conclusion: This is the largest detailed cohort study to date looking at individual risk factors for CRC in UC. Patients with PSC, pertinent macroscopic features (tubular, featureless, shortened colon or stricture) or persistent microscopic inflammation require intensive colonoscopic surveillance. In addition, the histological assessment of inflammation severity at the time of colonoscopy may be used to predict future CRN risk. Disclosure of Interest: None Declared